Analisis Faktor-Faktor Yang Berhubungan Dengan Partisipasi Dalam Program Pengelolaan Penyakit Kronis (Prolanis) Pada Pasien Diabetes Mellitus - Selina Citra Anastasya; Anita Shinta Kusuma; Sapto Haryatmo (STIKES Ngesti Waluyo, 2025)
The Chronic Disease Management Program (Prolanis) is a BPJS Health program aimed at improving the quality of life of people with chronic diseases, including Diabetes Mellitus (DM). Participant involvement is a key factor in the program’s success; however, not all participants engage optimally. This study aims to analyze the factors related to the participation of Prolanis participants with DM in the working area of Bejen Public Health Center. The study used an analytical, cross-sectional design, and the instrument used in this study was a questionnaire. The research sample consisted of all DM patients registered as Prolanis participants at Bejen Public Health Center, totaling 45 respondents, selected using the total sampling technique. The independent variables included knowledge, family support, illness perception, and perceived need, while the dependent variable was participation. Data analysis was performed using bivariate analysis with the Somers’ D test. The results showed that there was no significant relationship between knowledge and participation (p=0.164), nor between illness perception and participation (p=0.164). However, there was a significant relationship between family support (p=0.000; D=0.559) and program participation, and also between perceived need (p=0.048; D=0.351) and participation. The conclusion of this study is that family support and perceived need play an important role in improving the participation of Prolanis participants with DM. It is recommended that the health center enhance families' role in providing support and educate participants to strengthen their awareness of the importance of involvement in the program.